Turning a Blind Eye to Ratoon Stunting Disease of Sugarcane in Australia - Young, Anthony J (Plant disease, 2018)
The Australian sugar industry has never pursued genetic resistance to ratoon stunting disease (RSD), despite it being widely considered to be one of the most important diseases of sugarcane (Saccharum interspecific hybrids). This is because of a prevailing view that the disease is economically managed, and that no further action needs to take place. However, there is a range of epidemiological evidence that suggests that RSD is having a more significant impact than what is generally recognized. This review traces the factors that have led to an industry stance that is apparently without any scientific justification, and which has tended to downplay the significance of RSD on Australian sugarcane productivity, and thus has led to significant lost production. The consequences of this position are that RSD may be influencing broad but poorly explained issues such as commercial ratooning performance of existing varieties and the "yield decline" that has been subject to much scrutiny, if not much success in resolving the issue. Based on the available information, this review calls on the Australian sugar industry to prioritize selection for RSD resistance in the plant improvement program.